(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
The plant Asparagus racemosus is widely distributed in the Himalayan and sub-Himalayan regions of India. Based on preliminary reports, there is a lot of interest in using the roots of this plant for treating sexual disorders. In this study, the hydro-alcoholic and aqueous extracts of the roots of Asparagus racemosus were subjected to preliminary phytochemical screening which showed the presence of saponins, carbohydrates, glycosides and mucilages. The total extracts were tested for their aphrodisiac activity in experimental rats. The hydro-alcoholic extract of Asparagus racemosus root at higher concentration (400 mg/kg body weight) showed significant aphrodisiac activity on male wistar albino rats as evidenced by an increase in number of mounts and mating performance. On the other hand, hydro-alcoholic extract at lower dose (200 mg/kg. body weight) and aqueous extract (400 mg/kg body weight) showed moderate aphrodisiac property. Thus, in experimental rats, the results of the present study suggest that the extracts of Asparagus racemosus exert significant aphrodisiac activity. Further, detailed studies are needed to know whether in-vivo administration of the extracts is beneficial for patients suffering from sexual disorders.